STUDI ANALISIS KESULITAN MEMBACA PADA SISWA KELAS 2 SD NEGERI MERTAN 04 KABUPATEN SUKOHARJO TAHUN PELAJARAN 2025/2026 - Hidayatullah, Miftahul; Ratih Rasanawati, I Made (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: 1) describe the types of reading difficulties experienced by second-grade students of Mertan 04 Elementary School, Sukoharjo Regency in the 2025/2026 Academic Year, 2) find factors that influence reading difficulties in second-grade students of Mertan 04 Elementary School, and 3) identify teacher efforts in helping students overcome initial reading difficulties. The method used in this study is descriptive qualitative with a case study approach. The subjects of this study included the class teacher and eleven second-grade students. The results of the study indicate that: 1) initial reading difficulties in grade II students include difficulties in recognizing and distinguishing letters that look similar such as b-d, p-q, and m-n, difficulties combining letters into syllables and words, reading by spelling, and less fluent and intense in reading simple words and sentences; 2) factors that influence initial reading difficulties include internal factors such as low interest and motivation in reading, lack of memory, and low self-confidence, and external factors such as lack of support from the family environment, limited reading at home, and differences in students' abilities in understanding learning materials; 3) efforts made by teachers to help students overcome reading difficulties include providing individual reading guidance, inviting students to read regularly, using media and additional reading, and working together with parents to accompany students learning to read at home.